Analisis Kebijakan Pembelajaran PAI di Masa Pandemi: Peluang Dan Tantangan - Ely Novianti; Alda Rizka Fatkhia; Zalik Nuryana (Universitas Muhammadiyah Prof Dr Hamka, 2020)
This study aims to determine the impact of distance learning policies during the pandemic on Islamic education learning, the opportunities and challenges for Islamic education teachers at SMPN 1 Kretek. This study used qualitative methods with data collection techniques in the form of interviews and observations of Islamic education teachers at SMPN 1 Kretek. The impact of online learning policies makes teachers understand technology for learning media, understand student barriers in online learning, and provide solutions for students. What is done by SMPN 1 Kretek for learning is to use SMARTJITEK. SMARTJITEK is a special e-learning for SMPN 1 Kretek schools accessed via the web using the internet. However, even though they already have e-learning, Islamic religious education, the Whatsapp platform is used to provide convenience in the teaching process. The results of this study show that the implementation of distance learning PAI teachers must be alert and innovate so that the implementation of learning is carried out well.